1984
DOI: 10.1016/0042-6822(84)90275-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping of human cytomegalovirus genes: Identification of DNA sequences coding for a virion phosphoprotein of 71 kDa and a viral 65-kDa polypeptide

Abstract: Polyadenylated RNA was isolated from fibroblast cultures infected with human cytomegalovirus (HCMV) strain AD169 during the late phase of viral replication. The RNA was selected by hybridization to a series of cosmid clones containing the entire viral genome in partially overlapping segments. Translation of this RNA in a reticulocyte cell-free system allowed the mapping of virus specific polypeptides. Nine polypeptides synthesized in vitro comigrated with major virion structural proteins. An in vitro-translate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 34 publications
(23 reference statements)
1
65
1
Order By: Relevance
“…The most abundant phosphoprotein in laboratory strains of HCMV is the lower matrix protein (Gibson & Irmiere, 1984). From the location of the gene and from the DNA sequence it is clear that the protein originally described as glycoprotein 64 (gp64) of the Towne strain Pande et al, 1984) and the phosphoprotein 65 (pp65) of strain AD169 (Nowak et al, 1984a;Riiger et al, 1987) are the same. Both polypeptides map to the corresponding HindIII fragments H and N of strain Towne and fragments L, b and c of strain AD169.…”
Section: Phosphoproteinsmentioning
confidence: 96%
“…The most abundant phosphoprotein in laboratory strains of HCMV is the lower matrix protein (Gibson & Irmiere, 1984). From the location of the gene and from the DNA sequence it is clear that the protein originally described as glycoprotein 64 (gp64) of the Towne strain Pande et al, 1984) and the phosphoprotein 65 (pp65) of strain AD169 (Nowak et al, 1984a;Riiger et al, 1987) are the same. Both polypeptides map to the corresponding HindIII fragments H and N of strain Towne and fragments L, b and c of strain AD169.…”
Section: Phosphoproteinsmentioning
confidence: 96%
“…), anti-pUL99 (clone 10B4 -29, ref (23). ), anti-UL83 (clone 8F5, ref (24). ), and anti-UL82 (4F7, ref (25).…”
Section: Methodsmentioning
confidence: 99%
“…The protein ep65 has been shown to be synthesized at early times in HCMV-infected cells in the presence of DNA inhibitors such as Ara-C (Britt & Vugler, 1987), although at levels approximately 5% of those produced at late times (Geballe et al, 1986). It appears to be identifiable as the 64K to 65K protein described by several authors (Clark et al, 1984;Nowak et al, 1984;Pande et al, 1990;Somogyi et al, 1990), and shown by Britt & Vugler (1987) to be a delayed early phosphorylated protein. In parallel to a similar structural protein of HSV (Campbell et al, 1984), it could be considered as a potential regulatory protein initiating and controlling IE gene transcription (Britt & Vugler, 1987).…”
mentioning
confidence: 99%
“…(i) pp64-65, which is encoded by a gene located between map units 0.50 and 0-51 (Clark et al, 1984;Nowak et al, 1984;Britt & Vugler, 1987), is associated with protein kinase activity and represents the lower matrix protein (Roby & Gibson, 1986). (ii) pp67 is encoded by a gene located between map units 0.40 and 0-42, and also possesses protein kinase activity (Davis et al, 1984;Davis & Huang, 1985).…”
mentioning
confidence: 99%